PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN EKSPLOITASI (Studi Di DPMPPA Kota Jambi) - Rafikah, Rafikah; Adawiyah, Robi’atul; Habi, Nuraida Fitri; Hadi, Syamsu; Asiyah, Asiyah; Astuti, Riri (Jurnal Ilmiah Dinamika Hukum, 2024)
The phenomenon of child exploitation reached 147 cases in Jambi City from 2021 to 2022. The Jambi City Community Empowerment, Women and Child Protection (DPMPPA) Office as one of the institutions that has a technical role in implementing child protection norms, standards, procedures and criteria, also has several times found that there are various forms of exploitation carried out against children. This study aims to find out more about the causal factors and the efforts made in overcoming acts of exploitation of children in Jambi City. The research method is empirical juridical with data collection through observation, interviews, and deficiencies. The results showed that the exploitation of children in Jambi City was mostly done by their own parents due to various factors such as the economy, environment, culture and education. Efforts made to child victims of this exploitation are by providing assistance and guidance by the Jambi City DPMPPA.